Nano-scale MOSFET device modelling with quantum mechanical effects - CUMBERBATCH, ELLIS; UNO, SHIGEYASU; ABEBE, HENOK (European journal of applied mathematics, 2006)
The continuing down-scaling trend of CMOS technology has brought serious deterioration in the accuracy of the SPICE (Simulation Program with Integrated Circuit Emphasis) device models used in the design of chip functions. This is due to in part to hot electron and quantum effects that occur in modern nano-scale MOSFET devices [13, 25, 28, 33, 34]. The focus of this paper is on modeling quantum confinement effects based on the Density-Gradient (DG) model [6, 9, 14], for application in SPICE. Analytic 1-D quantum mechanical (QM) effects correction formulae for the MOSFET inversion charge and electrostatic potential are derived from the DG model using matched asymptotic expansion techniques. Comparison of these new models with numerical data shows good results.